AN ANALYSIS OF PRESUPPOSITION USED IN FIFT SHADES OF GREY BY E.L JAMES - GIANTIKA CHANDRA, DHONI (LANGUAGE HORIZON, 2016)
Abstract This study is a descriptive qualitative study where it is designed to describe the case of the study by words or sentences rather than numbers. The object of the study is presuppositions which is found in Fifty Shades of Grey Novel and the existence of the complication of presupposition’s interpretation in the utterances and the cause. The reason why the writer use presupposition on Fifty Shades of Grey novel as the main object of this study is to find out the types of presupposition, the intended meaning of presupposition and the function of presupposition that are used in the Fifty Shades of Grey novel. From data collected, the writer found 31 presuppositions and the most dominant type of presupposition that used is factive presupposition, it is shown from the data that there are 13 factive presupposition and 3 presuppositions for counter factual presupposition and there are 9 lexical presuppositions from data and 4 data for existential presupposition. In this study, the writer also try to describe the function or the significance of presupposition to find the meaning of utterances which expressed by the author to the reader. The most common of presupposition function which the writer found in this novel was as a tool for the author to share information and express their feeling through presupposition, it is because they need to deliver information that the writer believe the reader already known the intended meaning. Keywords: pragmatic, presuppositions, utterances, communication Abstrak Penelitianinimerupakanpenelitiandeskriptifkualitatif di manaiadirancanguntukmenggambarkankasusstudioleh kata-kata ataukalimatdaripadaangka. Objekpenelitianiniadalahpresuposisi yang ditemukandalam Fifty Shades of Grey Novel danadanyakomplikasiinterpretasipresuposisidalamucapan-ucapandanpenyebabnya. Alasanmengapapenulismenggunakanpengandaian di Fifty Shades of Grey novel sebagaiobjekutamadaripenelitianiniadalahuntukmengetahuijenispresuposisi, arti yang diinginkandaripresuposisidanfungsipresuposisi yang digunakandalam Fifty Shades of Grey novel. Dari data yang dikumpulkan, penulismenemukan 31 presuposisidanjenis yang paling dominandaripresuposisi yang digunakanpadaFift Shades of Greyadalahanggapanfaktif, terlihatdari data yang ada 13 presuposisifaktifdan 3 presuposisiuntuk counter faktualdanada 9 presuposisileksikaldari data dan 4 data untukpresuposisieksistensial. Dalampenelitianini, penulisjugamencobauntukmenggambarkanfungsiatausignifikansipresuposisiuntukmenemukanmaknadariucapan-ucapan yang diungkapkanolehpenuliskepadapembaca. Yang paling umumdarifungsipresuposisi yang penulisditemukandalam novel iniadalahsebagaialatdaripenulisuntukberbagiinformasidanmengekspresikanperasaanmerekamelaluipresuposisi, itukarenamerekaharusmemberikaninformasi yang penulispercayapembacasudahmengetahuimakna yang dimaksud. Kata kunci: pragmatis, presuposisi, ucapan, komunikasi